Study on type of magnetic suspension rotor groove and wear of drop touchdown bearing - Hu Lai; Jia Pengyang; Wang Zixi; Wang Yuming (Engineering Applications of Computational Fluid Mechanics)
The active magnetic bearing (AMB) is widely used in the field of flywheel energy storage system (FESS) in wind power generation. This study mainly studies the magnetic suspension rotor groove (MSRG) of FESS and the wear of drop touchdown bearing (DTB). The mathematical model of air gap magnetic field waveform on stator surface and Plath equation of control in air gap region were established. Contrastive analysis of conventional, second harmonic and third harmonic ‘petal-shaped’ MSRG in AMB. The life test of DTB on magnetic suspension rotor was carried out for 24000r/min and lasted for 1500 h. The second harmonic ‘petal-shaped’ MSRG could not only generate reluctance torque and increased the torque density of the motor, but also increased the fundamental component and excitation torque component by reducing the peak value of the magnetic field. The temperature ranges of front and rear DTB were ‘30℃–46℃’ and ‘26℃–40℃’, respectively. After service, the maximum thickness of metamorphic layer in the DTB raceway was 6 μm. After service, the content of Fe in the metamorphic layer of DTB raceway decreased by 10.11% and the content of C increased by 2.41%. Raceway hardness of DTB after service was 59.67 HV higher than that before service.